The intergenerational inequality of East Asian Economies under education premium: A comparative analysis based on ISSP2009 - Shouhao Li; Zhichen Lyu; Xinyi Gu (PLoS ONE, 2026)
Recent studies have verified that the welfare regime is an important factor influencing intergenerational inequality, with the conservative regime being the most immobile one among the three welfare regimes adopted by western developed countries. Compared with the west, the productivist welfare regime is classified for East Asian economies due to their restrained welfare provision. This paper aims to explore the intergenerational inequality under productivist welfarism and finds that, under a productivist regime, individuals exhibit lower intergenerational inequality than those under a conservative regime, both in terms of father-to-child socioeconomic status and in the influence of fathers’ socioeconomic status on children’s income. Further analysis, grounded in human-capital theory, suggests that the education premium exists under a productivist regime is linked, albeit partially, to this finding.